SAGBI bases for the Kernel of certain locally nilpotent K-derivations on polynomial rings. (São Paulo Journal of Mathematical Sciences, 2010)
In this paper is obtained an algebraic-computational property related to the theory of SAGBI bases for the specific case of the kernel of some locally nilpotent derivations on the polynomial ring in several variables over a eld of characteristic zero. The result achieved via explicit calculation is an algebraic characterization and a nite SAGBI basis for the kernel of a certain class of locally nilpotent derivations.